FOCUS In Emergency Room For Dyspnea: Bedside Diagnosis Is Now Possible For Pulmonary Embolism - (:unkn) unknown (My University, 2020)
Aim: It’s known that computed tomographic pulmonary anjiography (CTPA) is the gold standard in imaging techniques for pulmonary embolism (PE). Echocardiography and focused cardiac ultrasonography (FOCUS) are the most beneficial bedside diagnostic tools. Our aim was to determine the value of FOCUS in the diagnostic algoritm of pulmonary embolism.Materials and Methods: This study was designed prospectively in a tertiary medical center’s emergency medicine department. All the patients which were presented with dyspnea triaged with Emergency Severity Index triage criteria 1-2, after that if PE was involved in differential diagnosis and the patients whose had Wells score as moderate or high risk randomized for whether to carry out FOCUS or not. The patients who underwent CTPA were included to study. FOCUS protocol consisted of the views of parasternal long axis, parasternal short axis, subxiphoid and apical four chamber views. The ratio of Right ventricle to the left ventricle, right ventricular dilatation, septal flattening, septal paradoxal movement, right atrial and ventricular thrombus, vena cava inferior (VCI) and ejection fraction (EF) were evaluated from these views. Final diagnoses of patients and the statistical significance of FOCUS parameters in the diagnosis of pulmonary embolism was examined. Results: 102 patients were included in the study, of which 45 (44,1%) were women. Patients mean age was 63,8 -+ 15. PE was found as final diagnosis at the 60(%58,8) patients. The FOCUS parameters which were the ratio of right ventricle to the left ventricle over 0,9 [sensitivity %45(%32,12-%58,39) and specificity %80,95(%65,88-%91,40) (p=0,0069)], septal paradoxal movement [sensitivity %21,67(%12,07-%34,20) and specificity %95,24(%83,84-%99,42) (p=0,0182)], full VCI(>21 mm, %70) relation [sensitivity %28.33(%17.45, %41.44) and specificity %97.62(%87.43, %99.94) (p=0,0004)] were found as the most valuable. Conclusion: FOCUS could be a valuable diagnostic tool that saves lifes in unstable patients by making early diagnosis.

Amaç: Pulmoner Emboli(PE)’de altın standart görüntüleme yöntemi Pulmoner Anjiyografik Bilgisayarlı Tomografi (PABT) olarak bilinmektedir. Anstabil hastalarda yatak başı ekokardiyografi ve odaklanmış kardiyak ultrasonografi (FOCUS) en yararlı tanı araçlarındandır. Amacımız FOCUS’un akut PE tanı algoritmasındaki değerliliğini saptamak olacaktır. Gereç ve Yöntemler: Bu çalışma 3.basamak bir acil servis kliniğinde prospektif olarak dizayn edilmiştir. Acil Servise solunum sıkıntısı ile başvuran hastalar ESI triaj kriterlerine göre (kriter 1-2) triaj yapılmıştır ve bundan sonra ayırıcı tanısında PE varsa ve Well’s Skoru orta ve yüksek risk grubunda olanlara randomizasyon yapılarak yatak başı FOCUS yapılıp yapılmayacağına karar verilmiştir. PABT görüntülemesi yapılmış olan hastalar çalışmaya dâhil edilmiştir. FOCUS protokolü parasternal uzun aks penceresini, parasternal kısa aks penceresini, subksifoid pencereyi ve apikal 4 odacıktan penceresini içermiştir. Bu pencerelerden sol ventrikül fonksiyonu, sağ/sol ventrikül oranları, sağ ventrikülün dilatasyonu, septal düzleşme, septal paradoksal hareket, sağ atrial and ventriküler trombüs varlığı ve inferior vena kavayla ejeksiyon fraksiyonunun ölçümü değerlendirilmiştir. Hastaların son tanıları ve FOCUS’ta bulunan parametrelerin pulmoner emboli tanısında istatistiksel olarak anlamlılıkları incelenmiştir. Bulgular: Çalışmaya 102 hasta dâhil edilmiş olup, bunların 45 tanesi (%44,1) kadındır. Hastaların ortalama yaşı 63,8-+15 yıldır. PABT çekilen 102 hastanın 60(%58,8)’ında son tanı olarak PE saptanmıştır. FOCUS parametrelerinden; sağ ventrikülün sol ventriküle oranı [duyarlılığı %45(%32,12-%58,39) ve özgüllüğü %80,95(%65,88-%91,40) (p=0,0069)], septal paradoksal hareket [duyarlılığı %21,67(%12,07-%34,20) ve özgüllüğü %95,24(%83,84-%99,42) (p=0,0182)], dolu VCI(>21 mm, %70) ilişkisi [duyarlılığı %28.33(%17.45, %41.44) and özgüllüğü %97.62(%87.43, %99.94) (p=0,0004)], en değerli olarak görülmüştür. Sonuç: FOCUS erken tanıyı mümkün kılabilerek anstabil hastada hayat kurtaran değerli bir tanı aracıdır.
Nefes Darlığı için Acil Serviste FOCUS: Pulmoner Emboli için Yatak Başı Teşhis Artık Mümkün